PERAN DAN STRATEGI LEMBAGA KEUANGAN SYARIAH (STUDI KASUS) BMT SYARIAH ATTAQWA & BMT IKHTIAR - Arief Budi Santoso (Universitas Pamulang, 2018)
AbstractThe aim of this research is to know the role and Strategy of syaria cooperation as a finance institution in Indonesia. The research object are BMT At-Taqwa and BMT Ikhtiar. The research method used in this research are qualitative research, descriptive analysis by interviewing some of employees. By using data collection technique such as interviewing and observing primary informant (BMT At-Taqwa and BMT Ikhtiar Management) and secondary informant (Sharia Supervisory Council) for data validity.The result of this research showed that there were many fungtions from syaria cooperation to help people in Indonesia based on Islamic rules. Those adjustments can be seen from the steps of sharia strategic management taken from islam rules start from strategy formulating, strategy implementing, and strategy evaluating. The indicators of this research are the process of strategic management done by BMT At-Taqwa and Ikhtiar adjusted to J. David Hunger concept and Thomas L.Wheelen by looking forward from the evaluation. Keywords : Sharia Cooperation, Finance Institution